Cover Picture: Impaired Chaperone Activity of Human Heat Shock Protein Hsp27 Site‐Specifically Modified with Argpyrimidine (Angew. Chem. Int. Ed. 38/2016). Issue 38 (3rd August 2016) - Matveenko, Maria; Cichero, Elena; Fossa, Paola; Becker, Christian F. W.
Abstract : Non‐enzymatic variations of posttranslational modifications (nPTMs) form through reactions of electrophilic metabolites (here, in the eye) with nucleophilic protein side chains (arginine in the hourglass). Such modifications accumulate over time, but are poorly understood at the molecular level. In their Communication onpage 11397 ff., C. F. W. Becker and co‐workers report on the impact of the nPTM argpyrimidine on the structure and activity of a human chaperone protein. (Image: iStock.com/Dmytro Kozlov.)